Using biosensors for the early diagnosis of arboviruses: a scoping review - Vicente, Lígia Marques; Rodrigues, Rafaela Carla Piotto; Uehara, Silvia Carla da Silva Andre (Revista Brasileira de Ciência, Tecnologia e Inovação, 2024)
Mapping scientific knowledge about the development of biosensors to be used for the early diagnosis of arboviruses. Scoping review based on studies searched in Lilacs, PubMed, SciELO and Web of Science databases. Nineteen (19) articles were selected, in total. The selected studies presented different types of biosensors used to detect arboviruses and their variants, with emphasis on dengue and Zika viruses. Electrochemical, optical and plasmon resonance were the biosensors mostly used for the aforementioned purpose due to their little margin of error. They enable reliable and fast diagnosis processes, besides being easy to handle and its low cost. Biosensors capable of identifying arboviruses are not yet available in health services, since they still require advancements to be achieved at practical research stages.